Solar-Powered Pumping for Alleviating Energy Poverty: Sustainable Solutions for Agriculture Sector in Portugal - Alireza Zabihi; Tripura Pidikiti; L. N. Sastry Varanasi; Gauri Kalnoor; Iskender Akkurt; V. B. Murali Krishna (IEEE Access)
Sustainable Development Goal 7 highlights affordable and reliable energy access as a pervasive problem around the world, affecting millions of people struggling with energy poverty, and it hinders global social justice, economic prosperity, and quality of life. Addressing this problem is critical to achieving environmental stewardship and alleviating poverty. Green energies address energy poverty in nations that are already threatened. Solar systems are sustainable solutions for decentralizing clean energy. Photovoltaic (PV) minimizes emissions and dependency on fossil fuels. This study highlights the significance of RES integration in tackling energy poverty in industries. Coimbra, Portugal, is used as a case study to illustrate PV-powered irrigation networks and the agriculture sector. Results indicate the effectiveness of Portugal’s PV-powered pumping system, meeting 94.3% of water needs with an annual efficiency of 48.3%, and achieving a Net Present Value (NPV) of €22,469.73 and an Internal Rate of Return (IRR) of 74.24%, demonstrating strong economic viability over 20 years. With considerable electricity cost reductions and a strong return on investment, the solar-powered pumping system turns out to be a profitable project.